Agricultural extension, the Kenya experience: an impact evaluation - Gautam, Madhur (Washington, D.C. : World Bank, 2000)
This volume evaluates the impact of the Training and Visit (T&V) system of management, introduced in Kenya by the World Bank in 1982 as a pilot, based on a credible body of empirical evidence. It identifies the system's deficiencies and makes recommendations for improvement.
At head of title: World Bank Operations Evaluation Department.
Includes bibliographical references (p. 65-66).
oif 11/08/15
Loan
Keywords: Agricultural extension work; Kenya